Relación de altura total y comercial con el diámetro de los árboles en dos tipos de bosque en el distrito de Contamana, Loreto Perú - 2017 - Vela Diaz, Carmen Cecilia (2019)
This study deals with the determination of the relationship between total height and commercial height with the diameter of trees from two types of forest located in the district of Contamana, province of Ucayali, Loreto Region. Dasometric information of all trees of commercial species with DBH ? minimum cutting diameter were registered through a forest census. Results show excellent correlation between diameter-total height and diameter-commercial height in the low-terrace forest (better fit (S-curve), r = 0,949; r = 0,892 and R2 = 0,900; R2 = 0.796, respectively). The correlation between total diameter and height by species and type of forest is also excellent, where copaiba of the low-terrace forest shows the best fit (cubic), r = 0,966 and R2 = 0,934. The correlation between diameter and commercial height for species and for forest type is regular, where copaiba of the low-terrace forest shows the best fit (cubic) r= 0,703 and R2 = 0,494. The hypothesis is accepted that there exists a relationship between the total height and the commercial height and the diameter of the trees by type of forest.